COMPARATIVE ANALYSIS OF THE ANTHROPOMETRIC CHARACTERISTICS, PHYSICAL PREPAREDNESS AND TECHNICAL SKILLS OF 14-YEAR-OLD BASKETBALL PLAYERS – BOYS AND GIRLS - Mariana Borukova (Journal of Applied Sports Sciences)
Purpose: The purpose of this study was to describe some anthropometric characteristics, to trace the physical preparedness level and the technical skills of children (girls and boys) up to 14 years old participating in competitive basketball, to make comparative analysis of the average values of both totalities, and to find the relation and dependence between the anthropometric characteristics, physical preparedness and basketball skills of both sexes. Methods: One hundred twenty-nine children were subjected to study, out of which sixty-three basketball players (boys) at the age of 13 ± 0,7 and 66 basketball players (girls) at the age of 13 ± 0,5. Sport-pedagogical test was applied to the participants, and a probated and standardized test battery including twenty indicators was used. The basketball players participated in the test voluntarily, they received no money or financial compensation for their contribution and their anonymity was guaranteed. Data analysis: Statistical analyses were performed with SPSS-23 and variation, correlation and comparative analysis were made, t-criterion of Student and U-criterion of Mann-Whitney were used. Results: As we had supposed and as it was proven by the results for that group, the gender differences had a more substantial impact on some physical development indications and greater part of the physical preparedness indications. In favor of the boys these differences were more strongly expressed in their height, degree of body mass and horizontal stretch, while in favor of the girls the differences were in the functional capacity of the chest. Boys were fully favored as far as rapidity, speed abilities, explosive strength of the lower limbs were concerned. Conclusion: We have to note that the accumulated training experience and the biological ripening impact positively on the performance of young male and female basketball players. The results of this study showed that there were statistically significant differences between boys and girls in terms of technical skills (TS) only along two indicators.